The Effect of Educational Background on Preparation of Lesson Planning in Project-Based Blended Learning - Chornia Putrantasa; Siti Masitoh; Andi Mariono; Fajar Arianto; Shahrin bin Hashim (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study aims to analyze the effect of educational background on preparing learning plans in project-based blended learning. Method: The study used a quantitative research method with an experimental research type. The research subjects were 40 teachers, 20 teachers with particular education backgrounds, and 20 teachers not from special education. The data collection technique used a questionnaire to review the educational background. Data analysis used a homogeneity test, normality test, and hypothesis test. Results: Based on the research results, the research data is homogeneous and statistically normally distributed. The results of hypothesis testing show an influence of educational background on the preparation of lesson planning in project-based blended learning statistically. Further research can examine and research the influence of teacher education background in other fields of education, from early school to college. Novelty: This educational background is fundamental because this is where the ability or insight related to the teacher's competence can be reviewed. It is hoped that it is appropriate and the same as the field of education being taught, mainly so that there are no obstacles in the learning or teaching process.